What Types of Internet Services Make Adolescents Addicted? Correlates of Problematic Internet Use - Kim KM (Dove Medical Press, 2020)
Kyoung Min Kim,1 Haebin Kim,2 Jae-Won Choi,3 Soo Yeon Kim,4 Jun Won Kim5 1Department of Psychiatry, College of Medicine, Dankook University, Cheonan, Republic of Korea; 2Department of Psychiatry, Kyung Hee University Hospital, Seoul, Republic of Korea; 3Department of Psychiatry, Gyeongsang National University Hospital, Jinju, Republic of Korea; 4Department of Psychiatry, Pusan National University Hospital, Busan, Republic of Korea; 5Department of Psychiatry, Catholic University of Daegu School of Medicine, Daegu, Republic of KoreaCorrespondence: Jun Won KimDepartment of Psychiatry, Catholic University of Daegu School of Medicine, 3056-6 Daemyeong-4 Dong, Nam-gu, Daegu 705-718, Republic of KoreaTel +82 53 650 4332Fax +82 53 623 1694Email f_affection@naver.comPurpose: This study investigated the prevalence and correlates of problematic internet use (PIU) in a large sample of adolescents based on the type of internet service used.Materials and Methods: The study was conducted from 2008 to 2010, and 223,542 adolescents aged 12 to 18 years participated in the study. The participants responded to a self-report questionnaire including items for demographic factors, internet usage time, most used internet service and mental health. The PIU was assessed with the Internet Addiction Proneness Scale for Youth-Short Form.Results: The overall prevalence rate of PIU was 5.2%, and the prevalence rates stratified by sex were 7.7% in boys and 3.8% in girls. The distribution of most used internet services was significantly different across sexes. The most commonly used internet services were gaming (58.1%) in boys and blogging (22.1%) and messenger/chatting (20.3%) in girls. The odds ratio for PIU was significantly different according to the most used internet service; using the internet mostly for pornography compared to information searching had the highest odds ratio (4.526-fold higher). Depressive episodes, suicidal ideation, and suicidal attempts were significantly associated with higher odds ratios for PIU (1.725-, 1.747- and 1.361-fold, respectively).Conclusion: The present study identified clinically important information about PIU in adolescents. The distribution of PIU has different patterns based on sex and specific internet services. Studies of PIU with well-defined methodology and assessment tools for PIU of each specific internet service are needed.Keywords: addiction, adolescence, sex differences, internet usage